Chemical speciation of carbon in municipal solid waste incinerator residues - Ferrari, Stefano (Waste management (New York, N.Y.), 2002)
Incinerators do not achieve a complete mineralization of organic constituents of municipal solid waste. The solid residues (bottom ash, boiler ash and air pollution control residues) contain carbon which can be determined as total organic carbon (TOC). This work focuses on the TOC composition and its significance to the genesis and diagenesis of the solid residues. An analytical procedure is presented to characterize carbon species by different chemical and microscopic analytical methods. The procedure is based on two steps. In the first step a quantitative classification of TOC into four different carbon species (elemental carbon, water extractable organic carbon, dichloromethane extractable organic carbon and non extractable organic carbon) is performed to obtain a first survey of the TOC composition. Based on this survey a further characterization of individual carbon species is performed. The results of the qualitative and quantitative characterization of carbon species allow to postulate hypotheses on the influence of organic carbon on the long-term behavior of the solid residues